2021
DOI: 10.1128/jvi.02331-20
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Attenuation of Virulence of Tembusu Virus Strain PS Is Determined by an Arginine at Residue 304 of the Envelope Protein

Abstract: The Tembusu virus (TMUV) PS strain, derived by several passages and plaque purifications in BHK-21 cells, displays remarkedly lower virulence in Pekin ducklings relative to a natural isolate of TMUV, but the potential virulence determinants and the in vivo mechanisms for substantial virulence attenuation of the passage variant remain unknown. Here, we constructed a series of chimeric and mutant viruses and assessed their virulence using a 2-day-old Pekin duckling model. We showed that residue 304 in the envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…These assays demonstrated that the K291 and K295 residues are important for viral binding in human cell lines but not in insect cell lines [ 62 ]. The passage of an attenuated strain of TMUV shows that E-304 is very important to the neurovirulence and neuroinvasiveness of TMUV, and the charged condition of this amino acid plays a key role in the binding affinity between the E protein and GAGs; another study found a similar situation at the E-367 residue [ 59 , 60 ].…”
Section: The Key Amino Acids Of the E Protein Involved In Flavivirus Early Infectionmentioning
confidence: 99%
“…These assays demonstrated that the K291 and K295 residues are important for viral binding in human cell lines but not in insect cell lines [ 62 ]. The passage of an attenuated strain of TMUV shows that E-304 is very important to the neurovirulence and neuroinvasiveness of TMUV, and the charged condition of this amino acid plays a key role in the binding affinity between the E protein and GAGs; another study found a similar situation at the E-367 residue [ 59 , 60 ].…”
Section: The Key Amino Acids Of the E Protein Involved In Flavivirus Early Infectionmentioning
confidence: 99%
“…The BHK-21 cell-derived Y and PS strains of TMUV were isolated and propagated previously, which were shown to display high- and low-virulence for 2-day-old Pekin ducklings respectively ( 11 ). Parental backbone viruses rY and rPS were rescued from the full-length cDNAs of Y and PS respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the role of T cells in protection from TMUV infection and the molecular basis of T cell-mediated protection against TMUV remain largely uncharacterized. Earlier works in our laboratory showed that the natural isolate Y and the plaque-purified strain PS, which exhibited distinct virulence in a 2-day-old Pekin duckling model, elicited comparable levels of neutralizing antibody ( 11 ). In this study, we describe the comparative studies on cellular immune responses to Y and PS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the team of Yang et al worked with a variant of TMUV which developed attenuated virulence after several passages. Their work shed new light on the development of an effective vaccine against TMUV infection, determining that residue 304 of the E protein was essential for virulence and cell attachment [ 139 ]. However, despite the interest of these candidate vaccines, further investigations are needed to optimize certain aspects of vaccination such as the route of inoculation, the optimal number of inoculations to achieve the correct immunity or possible interactions with other animal vaccination programs.…”
Section: Clinical Features and Pathogenicitymentioning
confidence: 99%